Etoposide, cyclophosphamide, total-body irradiation, and allogeneic bone marrow transplantation for hematologic malignancies - Giralt, S.A.; LeMaistre, C.F.; Vriesendorp, H.M.; Andersson, B.S.; Dimopoulos, M.; Gajewski, J.; Van Besien, K.; Mehra, R.; Przepiorka, D.; Khouri, I.; Yau, J.; Kantarjian, H.; et al. (Journal of Clinical Oncology, 1994)
Purpose: To determine the efficacy and toxicity of etoposide, cyclophosphamide, and fractionated total-body irradiation (TBI) as the conditioning regimen for allogeneic bone marrow transplantation (BMT) in patients with hematologic malignancies. Patients and Methods: Seventy-nine patients underwent BMT from a human leukocyte antigen (HLA)-identical sibling using cyclosporine/methotrexate for graft-versus-host disease (GVHD) prophylaxis. Thirty-four patients had early leukemia (acute leukemia or lymphoblastic lymphoma in first remission, chronic myelogenous leukemia [CML], or refractory anemia [RA]), and 45 patients had more advanced disease. Patients received etoposide 1,500 mg/m2 on day -8, followed by cyclophosphamide 60 mg/kg/d on days -7 and -6, and 10.2 Gy of TBI administered in six fractions of 1.7 Gy given twice daily for 3 days from day -3 to -1. Donor bone marrow was harvested and infused on day 0. Results: Patients with early leukemia had a disease-free survival rate of 53% ± 9% and an overall survival rate of 57% ± 10% at 3 years. Patients with advanced disease had a disease-free survival rate of 15% ± 5% and overall survival rate of 17% ± 5%. The actuarial relapse rate for the early-leukemia group is 33% ± 9% versus 69% ± 9% for patients with more advanced disease. Severe toxicity was most frequently manifested as pulmonary hemorrhage followed by multiorgan failure and death. The 100-day mortality rate for the early- leukemia group was 10% versus 50% for patients with more advanced disease. Conclusion: The combination of cyclophosphamide, etoposide, and TBI is a relatively safe and effective preparative regimen for patients with early hematologic malignancies. Controlled trials are needed to evaluate critically this combination versus other standard preparative regimens. Greater toxicity was observed in patients with advanced disease, and this program does not appear to offer any advantage over other regimens.